3
$\begingroup$

How would you evaluate this if X1, X2 are independent exponentials?

I know what $min(X1,X2)$ is and what $max(X1,X2)$ is. However, while $min(X1,X2)$ is exponential with parameter (lambda1 + lambda2) -- the max is not.

Is the only way to proceed is to say:

1) Suppose $X_1 > X_2$. Then I find $Pr(R <= r) = Pr(X_1 - X_2 <= r)$ by doing a double integral. 2) Suppose $X_2 <X_1$. Then I find $Pr(R <= r) = Pr(X_2 - X_1 <= r)$ by doing a double integral. 3) Calculate the CDF as:

$Pr(X_1 - X_2 <= r) Pr(X_2 <= X_1) + Pr(X_2 - X_1 <= r)*Pr(X_1 <= X_2)$.

That should give me $Pr(R \leq r)$. I then would then differentiate with respect to r to get $F_R(r)$.

Is there perhaps a more clever way to do it?

Thanks!

$\endgroup$
  • $\begingroup$ @StefanHansen: That doesn't help. I then get that $Pr(max(X_1,X_2) < x) = [1- exp(-\lambda_1 x)][1-exp(-\lambda_2 x)]$. Then what? I can't subtract CDF's as $F(R \leq r) = F(max(X_1,X_2) - min(X_1,X_2)) \neq F(max(X_1,X_2)) - F(min(X_1,X_2))$ $\endgroup$ – user1357015 Oct 4 '14 at 20:53
  • $\begingroup$ One approach is to work out the distribution for $Y_i=X_i-X_{(1)}$, then try to find the distribution of $\max(Y_i)$, which it appears you know how to do. $\endgroup$ – Glen_b Oct 4 '14 at 21:20
  • 1
    $\begingroup$ It also might be helpful to note that $\max(X_1,X_2)-\min(X_1,x_2)=((X_1+X_2)/2+|X_1+X_2|/2)-((X_1+X_2)/2-|X_1+X_2|/2)=|X_1-X_2|$. $\endgroup$ – Julius Vainora Oct 4 '14 at 23:54
5
$\begingroup$

For any $\alpha > 0$, $P\{X > \alpha\} = e^{-\lambda \alpha}, P\{Y > \alpha\} = e^{-\mu \alpha}$ and since $X$ and $Y$ are independent, these are also the values of the conditional probabilities that $X$ and $Y$ exceed $\alpha$ given the value of the other random variable. Consequently, $$\begin{align} P\{R > z\}&= P\{\max(X,Y) - \min(X,Y) > z\}\\ &= P\{X > Y+z\} + P\{Y > X+z\}\\ &= \int_0^\infty P\{X > y+z \mid Y = y\}f_Y(y)\,\mathrm dy + \int_0^\infty P\{Y > x+z \mid X = x\}f_X(x)\,\mathrm dx\\ &= \int_0^\infty e^{-\lambda(y+z)}\cdot\mu e^{-\mu y}\,\mathrm dy + \int_0^\infty e^{-\mu(x+z)}\cdot\lambda e^{-\lambda x}\,\mathrm dx\\ &= e^{-\lambda z}\int_0^\infty \mu\cdot e^{-(\lambda+\mu)y}\,\mathrm dy + e^{-\mu z}\int_0^\infty \lambda \cdot e^{-(\lambda + \mu)x}\,\mathrm dx\\ \end{align}$$ Can you take it from here to get $P\{R > z\} = 1-F_R(z)$ and thus determine the density of $R$? You will get what is called a mixture of two exponential densities.

$\endgroup$
  • $\begingroup$ Hi, awesome, this works too :-). $\endgroup$ – user1357015 Oct 5 '14 at 6:42

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.